The Effect of Teacher Teaching Skills Against Learning Outcomes - Yadi Sumyadi; Umasih Umasih; Abdul Syukur (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Learning outcomes have an important role in the learning process. This is because learning outcomes can be used as a benchmark to find out how far the students have changed after receiving their learning experiences, observed and measured in the form of knowledge, attitudes and skills. Learning outcomes are often used as a measure to determine how far a person has mastered the material that has been taught. So, learning outcomes are abilities that students achieve after going through the learning process to determine mastery of the material that has been taught. The problem in this study is that most students still consider history lessons to be limited to memorizing so that they are less interested in history lessons. This can be a measure of the level of understanding of students towards certain materials that have been given. The purpose of this study was to determine how much influence the teaching skills of teachers have on student learning outcomes. The research method used in this research is ex post facto, which means after the fact, by taking survey data. The population and sample in this study were students at SMA Perguruan Rakyat 2 East Jakarta.